Germinación y morfología de la plántula de Hymenaea courbaril L. (Caesalpinaceae)* - Flores, Eugenia M (Universidad de Costa Rica, 1990)
Hymenaea courbaril is a leguminous species, common in dry lowlands of the Pacific Coast, although it grows well at higher altitude. The seeds are typically caesalpinaceous, with a hard seed coat, but they germinate well at temperatures aboye 23°C, in humid soil, without mechanical scarification. Germination is epigeal, phanerocotylar and begins 20-30 days after sowing. Seedling development is fast under greenhouse conditions and provides the possibility of obtaining numerous healthy and vigorous seedlings, which may be used in reforestation programs